Toward an Ethically Sensitive Implementation of Noninvasive Prenatal Screening in the Global Context - Mozersky, Jessica (The Hastings Center report, 2017)
Noninvasive prenatal screening using cell-free DNA, which analyzes placental DNA circulating in maternal blood to provide information about fetal chromosomal disorders early in pregnancy and without risk to the fetus, has been hailed as a potential “paradigm shift” in prenatal genetic screening. Commercial provision of cell-free DNA screening has contributed to a rapid expansion of the tests included in the screening panels. The tests can include screening for sex chromosome anomalies, rare subchromosomal microdeletions and aneuploidies, and most recently, the entire fetal genome. The benefits of this screening tool are generally framed, by both providers and commercial laboratories, as enhancing reproductive autonomy and choice by providing an earlier, simpler, and more accurate screening while potentially reducing the need for invasive follow-up testing. The majority of the literature has explored these issues empirically or conceptually from a European or North American vantage point, one that assumes normative priorities such as individual reproductive autonomy and the clinical availability of maternal health care or prenatal screening programs within which cell-free DNA screening is offered. While its implementation has raised both challenges and opportunities, very little is known about real-world experiences and the implications of the rapid introduction of cell-free DNA screening outside of North America and Europe, especially in low- and middle-income countries. To begin addressing this gap in knowledge, we organized a four-day international workshop to explore the ethical, legal, social, economic, clinical, and practical implications of the global expansion of cell-free DNA screening. We describe eight key insights that arose from the workshop.